2021
DOI: 10.3390/children8100853
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Recurrence and Complication Rates Following Laparoscopic Inguinal Hernia Repair among Preterm versus Full-Term Newborns: A Systematic Review and Meta-Analysis

Abstract: Background: Laparoscopic inguinal hernia repair (LHR) in children has been widely performed in the last decades, although it is still not sufficiently researched in preterm infants. This systematic review and meta-analysis compared the recurrence and complication rates following laparoscopic hernia repair among preterm (PT) versus full-term (FT) newborns. Methods: Scientific databases (PubMed, EMBASE, Scopus, and Web of Science databases) were systematically searched for relevant articles. The following terms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Most used quality indicators in pediatric surgery are mortality, morbidity, unplanned readmissions, and the incidence of postoperative complications [ 3 , 4 ]. Many of those, such as mortality and morbidity, are often not applicable to the pediatric population because the incidence of those events is too low in children [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most used quality indicators in pediatric surgery are mortality, morbidity, unplanned readmissions, and the incidence of postoperative complications [ 3 , 4 ]. Many of those, such as mortality and morbidity, are often not applicable to the pediatric population because the incidence of those events is too low in children [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…A minimally invasive laparoscopic approach has been well described as safe and effective method in many different conditions in children [28][29][30][31][32]. Several studies showed that percutaneous gastrostomy placement has more common major complications than the laparoscopic method [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Minimally invasive surgery has become very popular over the last 30 years. Minimally invasive surgery in the pediatric population was slow to advance, but due to the development of technologies and instruments adapted to newborns and small children over the last 20 years has rapidly expanded to include all major pediatric surgical procedures in infants and children [ 3 , 4 , 7 , 8 , 9 , 10 ]. The benefits to the patient are great, but the technical hurdles are many, because of the varied size and physiology of this patient population.…”
mentioning
confidence: 99%
“…Equipment and instruments used for minimally invasive procedures in the pediatric population are specially designed to allow safe access to the small abdominal or thoracic cavities, maintain an adequate working space and perform maneuvers with the same or even better safety and efficacy as in open procedures [ 4 , 7 , 8 , 10 ]. The diameter of instruments and telescopes varies from 2 to 10 mm depending on the procedure and child’s age [ 3 , 4 , 7 , 10 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation